Mechanical extraction of ferulic acid from banana stem waste - Siti Natrah, Ismail (2016)
The present of ferulic acid (FA) in plants attract the attention of many researchers, especially in food, pharmaceutical and cosmetic industries. Banana stem waste (BSW) was generated from banana plantation. In this study, FA was extracted from BSW by using sugarcane press machine. There were three objectives in this study. The first objective was to characterize the compositions of BSW and extracted BSW juice (EBJ). The characterization of BSW was done based on the compositions of moisture, lignin, cellulose and hemicellulose. For the EBJ, it was characterized based on the compositions of total phenolic and glucose. The second objective was to analyze factors affecting FA extraction from BSW. In factorial analysis, there were five factors were selected based on the preliminary study. The factors were part of stem, ultraviolet (UV) light pre-treatment, pre-treatment temperature, cycle of extraction and storage time of EBJ. Design Expert software was used for the experimental design. Two-level factorial design was applied for the factorial analysis. The FA was analyzed by using high performance liquid chromatography (HPLC). The third objective was to optimize the extraction of FA from BSW. The experimental table for the optimization was constructed by using central composite design (CCD). There were two factors chosen from the factorial analysis which were pre-treatment temperature and storage time of EBJ. The suggested optimum conditions that obtained during optimization were validated by using validation experiment at pre-treatment temperature 25 °C and storage time of EBJ at 24 h. The result that obtained concluded that the optimum FA yield was obtained at the suggested conditions. Therefore, the application of Design Expert software wascapable to obtain the optimum conditions and to improve the extraction of FA.